Remote Sensing practicals - Caetano, Mário (2021)
The main purpose of this manual is to prepare the student to carry out projects to extract information from satellite images for land monitoring. This manual guides the student to the acquisition of concepts of digital processing of satellite images through practical exercises. Various stages of a remote sensing project are covered, ranging the acquisition of satellite images, extraction of information with automatic classifiers, and the evaluation of the accuracy of the products obtained. The materials here included have been prepared so that the student can use them autonomously. This manual consists of three parts: (1) tutorial for obtaining satellite images on the Internet, (2) satellite image processing tutorial in ArcGIS, and (3) digital satellite image processing exercises in ArcGIS. In the first part the student learns how to obtain satellite images for a certain area. Second, the student learns how to execute in a specific software the most common procedures of digital image processing, such as creation of coloured composites, vegetation indices, supervised and unsupervised image classification, change detection, and thematic accuracy assessment. Finally, the third part includes practical exercises designed for the student to apply the procedures previously learned.